2021
DOI: 10.1109/jlt.2021.3119225
|View full text |Cite
|
Sign up to set email alerts
|

Design and Performance Estimation of a Photonic Integrated Beamforming Receiver for Scan-on-Receive Synthetic Aperture Radar

Abstract: Synthetic aperture radar is a remote sensing technology finding applications in a wide range of fields, especially related to Earth observation. It enables a fine imaging that is crucial in critical activities, like environmental monitoring for natural resource management or disasters prevention. In this picture, the scan-on-receive paradigm allows for enhanced imaging capabilities thanks to wide swath observations at finer azimuthal resolution achieved by beamforming of multiple simultaneous antenna beams. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…On the other hand, the remarkable flexibility demonstrated by microwave photonic technologies coupled with the SWaP budget reduction offered by PICs can lead to the implementation of optical beamforming networks (OBFNs) for wideband radar systems, leading to highly flexible SAR systems [27]. A study in [28] focuses on designing an integrated-photonics RF beamformer for a multi-beam SCORE-SAR system in satellite-based Earth observation in the framework of the project SPACEBEAM. The research project focuses on hybrid integration of InP, containing the active components, and TriPleX chips which include the passive components and the Blass matrix implementing the beamforming network.…”
Section: Space Score-sar System With Integrated Photonic Beamformingmentioning
confidence: 99%
“…On the other hand, the remarkable flexibility demonstrated by microwave photonic technologies coupled with the SWaP budget reduction offered by PICs can lead to the implementation of optical beamforming networks (OBFNs) for wideband radar systems, leading to highly flexible SAR systems [27]. A study in [28] focuses on designing an integrated-photonics RF beamformer for a multi-beam SCORE-SAR system in satellite-based Earth observation in the framework of the project SPACEBEAM. The research project focuses on hybrid integration of InP, containing the active components, and TriPleX chips which include the passive components and the Blass matrix implementing the beamforming network.…”
Section: Space Score-sar System With Integrated Photonic Beamformingmentioning
confidence: 99%
“…This motivates future work to implement MWP processors that simultaneously achieve multiple RF processing functionalities in one optimised MWP link. Reza et al performed a theoretical analysis of a fully-integrated MWP beamformer that combines frequency conversion and phase shift beamforming [44]. Through simulations they showed that the overall RF link gain of the multi-functional MWP device was comparable to single function MWP devices, essentially halving the link gain penalty by distributing it between two RF processing functionalities.…”
Section: B Integrated Platforms and Rf Link Performancementioning
confidence: 99%
“…Chip-based MWP devices have enabled demonstrations of numerous RF processing functionalities that could form the basis of future element-level processing required for PAAs, including agile RF filters [28], [29], phase shifters [30], [31] and true time delays (TTDs) for beam steering functionality, [32]- [34], frequency converters that interface between the operating RF and baseband frequencies [35], [36], and microwave sources [37]- [40]. Initial demonstrations of MWP beamforming networks highlight the potential for implementing chip-based beamforming for PAAs [32], [34], [41]- [44], expanded on below.…”
Section: Introductionmentioning
confidence: 99%
“…If only a single moving beam is needed, a simple corporate network structure is sufficient to realise the OBFN, such as in [31][32] [33][34] [35][36] using different PSs and TTD implementations. Figure 3 and 4 illustrate two potential solutions for extending the network to employ more simultaneous beams [12][29] [37]. The blass matrix architecture is especially suited to the PAFR design since there will be little to no overlap in the beams.…”
Section: Sar Antenna Configurationmentioning
confidence: 99%
“…Examples are dispersive SCORE, multi-beam SCORE, and Staggered SAR which make extensive use of a digital beamforming (DBF) paradigm [6] [7][8] [9]. However, recent developments in photonic technologies have made photonic beamforming (PBF) a potential analogue contender to DBF methods [10] [11] [12]. Indeed, many features of optical beamforming networks (OBFN), such as small relative bandwidth, near frequency agnostic operation in SAR frequency bands, low power consumption and low computational requirements, make their implementation in SAR systems an enticing prospect [10] [13].…”
Section: Introductionmentioning
confidence: 99%